Suomen teollisen teknologian, tuotannon ja työllisyyden suhteellinen erikoistuminen - Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2010)
This study analyzes trends in specialization of the Finnish industry since the 1980s. Low technology industries, such as pulp and paper, have had traditionally a large proportion of the Finnish industrial output. During the recent decades their share of output has decreased significantly and Finland has specialized more and more in high technology industries, especially in ICT. The pattern of the Finnish revealed technological advantage with focus on ICT, and pulp and paper technologies differs from the pattern of the revealed technological advantage of many other countries. Internationally compared Finland has some technological advantage also in special purpose machinery, such as papermaking machines, special purpose vessels, elevators and transfer equipments, and in basic metals.
Keywords: L16; L60; N60; O30; 330; Finland; manufacturing; production; technology; employment; specialization; Technischer Fortschritt; Standortwettbewerb; Beschäftigung; Industrie; Branche; Finnland